1982
DOI: 10.1111/j.1744-7348.1982.tb01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Varietal differences in uptake of 32P labelled phosphate in clover plus ryegrass swards and monocultures

Abstract: S U M M A R YLolium perenne cv. S.23, L. multijlorum cv. RvP, and Trifolium repens cvs S. 184 and Olwen, were grown in mixed sward and monoculture during 1979. Whereas in mixtures grass roots absorbed more 32P than clover roots, in monoculture clover generally absorbed more 32P than grass roots. This showed that grass was a very strong competitor for uptake in mixed swards.Clover and grass monocultures absorbed most 32P from 10 or 15 cm depth in the soil, while grass in mixtures absorbed most 32P at 22.5 cm de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
4
5
0
Order By: Relevance
“…The clover variety Olwen produced more dry matter than SI84 at the lowland site and it also took up more '^N than SI84. This resembles the results of "P labelling experiments with the two varieties (Goodman and Collison, 1982). Over the whole summer season, N fixation, measured by isotope dilution, was greater in Olwen than in S184, but in September 1983 acetylene reduction was greater in SI 84 than in Olwen.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The clover variety Olwen produced more dry matter than SI84 at the lowland site and it also took up more '^N than SI84. This resembles the results of "P labelling experiments with the two varieties (Goodman and Collison, 1982). Over the whole summer season, N fixation, measured by isotope dilution, was greater in Olwen than in S184, but in September 1983 acetylene reduction was greater in SI 84 than in Olwen.…”
Section: Discussionsupporting
confidence: 81%
“…The isotope dilution equation which was used assumed that the ratio of fertilizer N uptake: soil N uptake was similar in grass and clover (Vose, 1980;Rennie, 1984). This overcomes the problem of allowing for the different root sizes known to exist between grass and clover (Goodman and Collison, 1982).…”
Section: Isotope Determinationmentioning
confidence: 99%
“…In cut plots, less than 40% of total root length has been found in the top 10 cm (Mackie-Dawson and Atkinson, 1991) which is in agreement with the proportion of 32P uptake activity by a grass/clover sward measured to I 0 cm (Goodman and Collison, 1982). In cut plots, less than 40% of total root length has been found in the top 10 cm (Mackie-Dawson and Atkinson, 1991) which is in agreement with the proportion of 32P uptake activity by a grass/clover sward measured to I 0 cm (Goodman and Collison, 1982).…”
supporting
confidence: 69%
“…Goodman and Collison (1982), using 32 P tracers, found that ryegrass was a strong competitor for P while other studies indicate that grass and clover might absorb similar amounts of 32 P (see e.g., Acuna and Wilman Fig. 4 Relations between accumulated N, P and K in the herbage at each sampling over 2 years and under varying supply of N, P and K (n = 224) 1993).…”
Section: Competitionmentioning
confidence: 95%